The Influence Of Supervison, Workload and Work Stress to The Performance Of Inpatient Installation Nurses at Murni Teguh Memorial Hospital Medan - Sri Wahyuni Nasution; Ermi Girsang; Widya Panduwinata (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The many demands of the community with nursing services and the emergence of competition in many health service facilities urge hospital management to always improve nursing services through improving nurse performance. This is because nurses are the largest number of health workers and are on duty for 24 hours to serve patients, especially nurses who are in charge of providing nursing services in inpatient installations. This research is a quantitativ research with a cross sectional approach. This study aims to analyze the effect of supervision, workload and work stress on the performance of inpatient installation nurses at Murni Teguh Memorial Hospital Medan. The population is all health workers (nurses) on duty in the Inpatient Installation totaling 224 people and all of them are sampled. Data collection techniques through questionnaire dissemination, documentation and literature study. The analysis method uses univariate, bivariate and multivariate analysis using multiple linear regression equations. The results showed that supervision, workload and work stress affected nurse performance and the dominant supervision variables influenced. The conclusion of the study was that supervision, workload and work stress affect the performance of Inpatient Installation nurses at Murni Teguh Memorial Hospital Medan. It is recommended that the head of the room should provide regular supervision in an effort to guide and direct nurses so that they have good competence in carrying out nursing service duties more effectively and efficiently.Keywords: Nurse Performance, Head Of Space, Supervision, Workload, Work Stress.